2019
DOI: 10.18632/aging.102285
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate control of thyroid hormones sensitizes to hepatocarcinogenesis and unhealthy aging

Abstract: An inverse correlation between thyroid hormone levels and longevity has been reported in several species and reduced thyroid hormone levels have been proposed as a biomarker for healthy aging and metabolic fitness. However, hypothyroidism is a medical condition associated with compromised health and reduced life expectancy. Herein, we show, using wild-type and the Pax8 ablated model of hypothyroidism in mice, that hyperthyroidism and severe hypothyroidism are associated with an overall unhealthy status and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 64 publications
0
34
1
1
Order By: Relevance
“…As opposed to other experimental models of hypothyroidism (Hine et al, 2017;Umezu et al, 2020), we found that the PAX8 heterozygous mice faithfully recapitulate the phenotype of humans with hypothyroidism, including insulin resistance, increased white adipose tissue (WAT) mass, and increased triglyceride content in skeletal muscle and liver (Lopez-Noriega et al, 2019). Similar to humans, these mice also exhibit reduced basal metabolic rate and obesity while maintaining normal energy intake.…”
Section: The Molecular Mechanisms Of Exceptional Longevitymentioning
confidence: 62%
See 1 more Smart Citation
“…As opposed to other experimental models of hypothyroidism (Hine et al, 2017;Umezu et al, 2020), we found that the PAX8 heterozygous mice faithfully recapitulate the phenotype of humans with hypothyroidism, including insulin resistance, increased white adipose tissue (WAT) mass, and increased triglyceride content in skeletal muscle and liver (Lopez-Noriega et al, 2019). Similar to humans, these mice also exhibit reduced basal metabolic rate and obesity while maintaining normal energy intake.…”
Section: The Molecular Mechanisms Of Exceptional Longevitymentioning
confidence: 62%
“…which have a direct disorder in thyroid tissue leading to a mild hypothyroidism, have a ~ threefold increased incidence of liver cancers (Lopez-Noriega et al, 2019). In principle, since hepatocarcinogenesis is a multistep process that originates from premalignant lesions, the severity of hypothyroidism and the effectiveness of treatments to normalize TH function might affect the risk to develop HCC.…”
Section: The Alterations Of Thyroid Hormone Function and Cancermentioning
confidence: 99%
“…Additionally, these animals showed a reduction in the percentage of β-cells in the islets as an effect of the mild hypothyroidism that they develop with age since Pax8 is not expressed in adult mice islets [123]. Moreover, in a comparative transcriptome analysis of the islets of Pax8 +/and wt mice we observed a decrease in master regulators of antioxidative processes, such as NRF2 in the hemizygous mice, supporting the requirement of adequate THs levels to preserve/protect β-cell integrity against oxidative stress damage [123]. Altogether these data suggest that PAX8 during pregnancy may have a dual role in glucose homeostasis: On one hand it will favor β-cell survival by enhancing β-cells resistance against apoptosis and stimulating the maintenance of a local anti-inflammatory milieu in the pancreas while on the other hand ensure systemic levels of TH, an important stimulator of insulin secretion and glucose clearance as well as protecting β-cells from environmental stressors (Figure 2).…”
Section: Pax8 a Pregnancy-dependent Islet Transcription Factor With mentioning
confidence: 99%
“…Nevertheless, since TH levels in these animals remain unaltered when compared to control wild type (wt) littermates, we expect that a genetic compensation for Pax8 hemizygosity takes place in Pax8 +/− animals, hindering the development of any alteration during pregnancy [120]. Nevertheless, male Pax8 +/− mice (8 and 24 months-old animals) with age exhibit a mild but significant decrease in circulating T4 levels correlating with mild glucose intolerance and increased insulin resistance [123], a phenotype resembling T2DM. Additionally, these animals showed a reduction in the percentage of β-cells in the islets as an effect of the mild hypothyroidism that they develop with age since Pax8 is not expressed in adult mice islets [123].…”
Section: Pax8 a Pregnancy-dependent Islet Transcription Factor With mentioning
confidence: 99%
See 1 more Smart Citation